2020
DOI: 10.1091/mbc.e19-12-0719
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial tissue geometry directs emergence of bioelectric field and pattern of proliferation

Abstract: Patterns of proliferation are templated by both gradients of mechanical stress as well as by gradients in membrane voltage (Vm), which is defined as the electric potential difference between the cytoplasm and external medium. Either gradient could regulate the emergence of the other, or they could arise independently and synergistically affect proliferation within a tissue. Here, we examined the relationship between endogenous patterns of mechanical stress and the generation of bioelectric gradients in mammary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 69 publications
1
23
2
Order By: Relevance
“…Inhibition of Ca 2+ influx reduces YAP phosphorylation and increases YAP nuclear localization. In a study of the relationship among patterns of mechanical stress, bioelectric field and proliferation, Silver et al (2020) found that mechanical stress gradients in mammary epithelial tissues of defined geometry lead more YAP/TAZ nuclear localization in cells at the tissue periphery than the center region. This phenomenon was accompanied by an increase of Ca 2+ level in cells at this region.…”
Section: Ca 2+ Signaling Activates the Hippo Pathwaymentioning
confidence: 99%
“…Inhibition of Ca 2+ influx reduces YAP phosphorylation and increases YAP nuclear localization. In a study of the relationship among patterns of mechanical stress, bioelectric field and proliferation, Silver et al (2020) found that mechanical stress gradients in mammary epithelial tissues of defined geometry lead more YAP/TAZ nuclear localization in cells at the tissue periphery than the center region. This phenomenon was accompanied by an increase of Ca 2+ level in cells at this region.…”
Section: Ca 2+ Signaling Activates the Hippo Pathwaymentioning
confidence: 99%
“…Biochemical signals may not be sufficient to drive the whole morphogenetic process. Integration with mechanical force and bioelectric signals have been implicated in regulating tissue morphogenesis (McLaughlin and Levin, 2018;Muncie and Weaver, 2018;Silver et al, 2020). To dissect out the morphogenetic control of tissue patterning, we chose a model consisting of a population of mini-organs.…”
Section: Discussionmentioning
confidence: 99%
“…Review associated with proliferation, apoptosis, or differentiation (Silver et al, 2020). Bioengineering tools can interact with and spatially pattern endogenous electric fields to shepherd collective cell motility in a process known as electrotaxis (Zajdel et al, 2020).…”
Section: Stem Cell Reportsmentioning
confidence: 99%
“…Besides morphogen signaling, electrical fields created through plasma membrane depolarization can be transmitted between cells via gap junctions or ion channels. Changes in membrane potential can then determine intracellular ion concentrations, affecting signaling networks associated with proliferation, apoptosis, or differentiation ( Silver et al., 2020 ). Bioengineering tools can interact with and spatially pattern endogenous electric fields to shepherd collective cell motility in a process known as electrotaxis ( Zajdel et al., 2020 ).…”
Section: Engineering Organogenesismentioning
confidence: 99%